Factors Affecting Financial Literacy Rate of Millennial in Malaysia - Nahar, Amar Imran Mohd; Shahrul, Siti Nur Shamira; Rozzani, Nabilah; Saleh, Siti Khadijah (International Journal of Publication and Social Studies, 2022)
Without being informed of financial management skills, many people are struggling financially as they are unaware of how to plan and manage money to make wise decisions regarding their finances. They are usually careless with spending money and do not plan effectively for their future. Most times, they would rely on cash in hand rather than doing effective planning to save or invest. Improper and inadequate planning can be a result of lacking financial knowledge and low literacy. This study investigates several factors of education, income, marital status, upbringing and influence, as well as its impacts toward financial literacy rate among millennials in Malaysia. This study employs quantitative research with primary data gathered using questionnaire from millennials residing in Malaysia. Results and findings of this study indicates that there is positive and significant relationship between education level and level of income with financial literacy rate of millennials in Malaysia.